Reinsurance of national unemployment benefit schemes - Beblavy, Miroslav; Gros, Daniel; Maselli, Ilaria (Brussels, 2015)
"This study is a contribution to the debate around the creation of an unemployment insurance scheme for the EU/euro area by proposing an alternative mechanism to the Europeanisation of national insurance schemes. The authors make the case for a reinsurance mechanism and show that such a system delivers, for a small average contribution, large shock-absorption capacities. At the same time, due to a threshold issue, it is not suitable for EU-level absorption of small national shocks. It is rather meant to deliver a large punch once activated, which should occur only in case of MAJOR events for the labour market. Had such a scheme been in place in the EU during the period 2000-2012, it would have been triggered 40 times."